Upaya Hukum Kepolisian Daerah Lampung dalam Penanggulangan Tindak Pidana Penyalahgunaan Bahan Bakar Minyak (BBM) - Bambang Hartono (Law Faculty of Universitas Bandar Lampung, 2013)
The emergence of the issue of misuse of fuel there are still those who perform illegal activities by abusing the fuel oil. Police as the executor of the government to enforce the law would need to take stern action against the perpetrators of the abuse of fossil fuels, the police are required to do a quick, responsive and appropriate in dealing with perpetrators of abuse fuel. Crime prevention efforts abuse (BBM) conducted POLDA Lampung and inhibiting factors in the response effort POLDA Lampung Crime fuel such abuse. Preventive efforts, namely direct action to prevent the abuse or misuse of fuel. Repressive efforts, which is a series of activities aimed towards action in criminal cases that the disclosure has occurred. Advice, that in the face of an increasingly complex task of the police themselves especially Lampung Police have to seek improvements in overall good that comes from within and from outside, such as improving police performance support facilities are located in the field. Whether its the procurement of communication equipment or operational support vehicles.